Handbook of vocational education and training : foundations for transforming the nation - Sheth, Jagdish N. [Verfasser]; Shome, Samik [Verfasser] (Routledge, Taylor & Francis Group, 2025)
"Vocational education and training (VET) are major stepping stones in the development journey of any nation. A carefully structured and implemented VET system ensures skill development and equips the existing and prospective workforce with the necessary technical proficiency, thereby reducing unemployment and increasing productivity. This handbook is designed to provide the readers with a comprehensive understanding of the ways in which VET has been implemented in both highly developed and developing countries around the globe, including Germany, Japan, China, India, and countries in Africa and Latin America, among others. It looks at how VET plays a crucial role in empowering a nation, acts as a comparative advantage, and contributes to nation-building. In the process, it highlights the best practices and fallacies related to VET and showcases how effective vocational training can allow countries to confront existing deficits in employment and decent work. This detailed handbook will be of interest to policymakers, government officials, and corporate executives working in education, education policy, curriculum, teaching and learning, adult education and lifelong learning, and classroom practice. It will also be valuable to technical education students and those working with executive training programmes, public sector enterprises and NGOs related to VET." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: S System beruflicher Bildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.1 Afrika; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; I 2.3.4 Asien; I 2.3.5 Australien, Ozeanien; 370; Berufsbildung; Berufsbildungssystem; Internationaler Vergleich; Afrika; Australien; China; Bundesrepublik Deutschland; Großbritannien; Indien; Japan; Lateinamerika; Skandinavien; Südkorea; Südostasien; USA